Community-based information system in Sapang Maisac Evacuation Center (Mexico, Pampanga) an innovative practice - Macale, Victoria B. (1998)
This case study is focused on the importance of establishing a Community-Based Information System (CBIS) in Sapang Maisac Evacuation Center (SMEC) in Mexico, Pampanga. Generally, it sought to determine the appropriate information, education, and communication needs and services that would enhance the knowledge, skills and attitude of the people in the community. Specifically, it aimed to: a) determine the socio-demographic profile of SMEC with regards to age, sex, civil status, population, literacy level, educational status and occupational patterns; b) find out their reactions to the idea of establishing a CBIS in their area; c) develop a community-based information system that would empower themselves and determine their own meaningful development; d) identify the structure that would enrich the initiative, the innovation, and the commitment of the community; e) identify and evaluate the available resources that would improve the socio-economic condition and the livelihood projects of the community and that would develop effective and efficient means to utilize the available resources; f) identify government organizations (GOs) and non-governmental organizations (NGOs), schools, health centers and other interested institutions that would support the interests and needs of the community; and g) explain the role of CBIS towards capability-building.